Dry sliding wear behavior of hot forged and annealed Cu-Cr-graphite in-situ composites - Gautam R.K.; Ray S.; Sharma S.C.; Jain S.C.; Tyagi R. (My University, 2025)
In the present investigation Cu based composites have been developed through solidification processing by addition of a fixed amount of Cr and three different amounts of graphite viz. 2, 3 and 4. wt.%. All of the cast composites have been hot forged and annealed. Dry sliding friction and wear behavior of all the composites in as cast, hot forged and annealed conditions has been investigated by sliding against a counterface of SAE 4615 steel disc under ambient conditions using a pin-on-disc machine. The sliding wear tests have been conducted at four different normal loads 10, 20, 30, and 40. N and a constant sliding speed of 0.786. m/s. The primary focus of the study is to understand the effect of hot forging and annealing after hot forging, on the wear characteristics of these composites. For a given normal load, the cumulative volume loss increases linearly with increasing sliding distance for all materials. The wear rate has also been found to increases linearly with increasing normal load. Wear rate of Cu-4Cr-4G composite is significantly lower than that of all other materials either hot forged or annealed. Average coefficient of friction decreases with increasing the normal load and the graphite containing composite shows the lower average coefficient of friction than the other materials. Worn surface of the pin specimen show significant formation of transfer layer for hot forged and annealed Cu-4Cr-4G composite. © 2011 Elsevier B.V.